How Is Teacher Performance in Indonesia Today? Examining the Mediating Role of Work-Life Balance - Rumijati, Aniek; Wurianto, Arif Budi; Hakim, Arif Rahman (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The quality of teacher performance is very important today because it directly impacts student learning outcomes and the success of overall educational goals. Ensuring teachers receive support and continuous development is key to maintaining high educational standards. Therefore, this study aims to analyze the influence of workload and perceived organizational support (POS) on teacher performance mediated by work-life balance (WLB). To gather data for this study, which employs an explanatory quantitative methodology, 185 elementary and high school teachers in Malang City were given an online questionnaire. Data analysis was processed using the Structural Equation Modelling (SEM) technique with SmartPLS software. The findings revealed that workload did not affect WLB and teacher performance. POS affected WLB and teacher performance, and WLB influenced teacher performance. Meanwhile, workload does not affect teacher performance through WLB, but WLB can mediate the influence of POS on teacher performance. These findings show that to improve teacher performance, schools must focus more on increasing perceived organizational support rather than workload. Perceived organizational support can improve work-life balance and overall performance. Workload should be managed through policies that ensure balanced distribution and institutional support. Schools and policymakers must provide flexible work arrangements and professional development to enhance work-life balance and teacher performance.